Base excess as a predictor of neonatal mortality in neonatal sepsis - K. P., Sushrutha; M. , Hamsa; N., Lingaraju; C. , Sampath Kumar (International Journal of Contemporary Pediatrics, 2023)
Background: Neonatal sepsis is responsible for approximately 15% of all neonatal deaths in the world. Despite of availability in advanced medical healthcare facilities for mother and neonates, incidence of mortality secondary to sepsis especially in developing countries like India is more common. Metabolic acidosis is the most common form of acid base imbalance in neonatal sepsis which can be analyzed with increased levels of base excess. Hence early diagnosis of neonatal sepsis can be done by determining base excess. Methods: This is a prospective observational study conducted in NICU at Cheluvamba Hospital, Mysore. 73 term neonates with suspected sepsis were enrolled in the study who were on regular follow-up and treatment till death/discharged from NICU. Base excess value is obtained from the arterial blood gas analysis from each subject and it was compared with survivor and non-survivor group along with other study parameter Results: Out of 73 subjects, incidence of non survivors group with severe increase in base excess is 75%. To predict the mortality, we compared it with standard base excess which showed the prediction of more than 60%, with significant AOC (0.827) of very near to one in ROC curve, with statistically significant (p<0.001) sensitivity of 92.59%, specificity of 63.04%, positive predictive value of 59.5%, negative predictive value of 93.5%. Conclusions: In present study we have proved that base excess is an important parameter for the early diagnosis and for early intervention in neonatal sepsis.